2009
DOI: 10.1073/pnas.0901419106
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition preference for and positional avoidance of acetic acid provide a model for competing behavioral drives in Drosophila

Abstract: Selection of appropriate oviposition sites is essential for progeny survival and fitness in generalist insect species, such as Drosphila melanogaster, yet little is known about the mechanisms regulating how environmental conditions and innate adult preferences are evaluated and balanced to yield the final substrate choice for eggdeposition. Female D. melanogaster are attracted to food containing acetic acid (AA) as an oviposition substrate. However, our observations reveal that this egg-laying preference is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
243
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(262 citation statements)
references
References 34 publications
(38 reference statements)
19
243
0
Order By: Relevance
“…Sensitivity to acetic acid is expressed in D. melanogaster adults and larvae (Hoffmann and Parsons 1984;Cobb 1999;Ruebenbauer et al 2008;Joseph et al 2009), supporting the idea that this compound is of ecological relevance. Acetic acid probably serves as a cue for the presence of fermenting fruit and other substrates used as food or oviposition sites.…”
Section: Trapping Study Of Diel Flight Period In the Laboratorymentioning
confidence: 58%
See 1 more Smart Citation
“…Sensitivity to acetic acid is expressed in D. melanogaster adults and larvae (Hoffmann and Parsons 1984;Cobb 1999;Ruebenbauer et al 2008;Joseph et al 2009), supporting the idea that this compound is of ecological relevance. Acetic acid probably serves as a cue for the presence of fermenting fruit and other substrates used as food or oviposition sites.…”
Section: Trapping Study Of Diel Flight Period In the Laboratorymentioning
confidence: 58%
“…Interestingly, Joseph et al (2009) (Table 2). It will be rewarding to study the representation of defined blends of synthetic compounds in comparison with complex authentic odors such as vinegar.…”
Section: Trapping Study Of Diel Flight Period In the Laboratorymentioning
confidence: 99%
“…1), and the oviposition and viability of flies (25 females and 20 males) were quantitatively investigated. When compared to conventional oviposition assays, our technique has provided a Surface quality, texture, and chemistry have been shown to have significant effects on flies' oviposition, 24,25,30,31,[33][34][35][36][37] however, the required area of exposure to agar substrate, in order to keep a population of fruit flies alive and to induce them to lay their eggs naturally (i.e., similarly to pure agar substrates) were not investigated. Accordingly, our aim was to quantitatively investigate the effects and the threshold values of surface exposure area on oviposition of fruit flies using our PDMS membrane patterning technique.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have likewise shown ovipositional preferences towards chemicals such acetic acid and limonene but avoidance from harmful ones like geosmin. 24,36,37 These techniques and studies have greatly enhanced our overall understanding of oviposition behaviour. However, they lack the accuracy, sensitivity and control, as well as the adequate level of repeatability that is required for parametric and quantitative investigation of viability and oviposition of fruit flies on agar substrates, especially in response to precise variations in surface exposure area and physical size of the oviposition site as well as the chemical and mechanical properties of the agar substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation